2021
DOI: 10.3390/vaccines9121472
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Novel Cysteine Protease Inhibitor from Poultry Red Mites: Potential Vaccine for Chickens

Abstract: Poultry red mite (PRM; Dermanyssus gallinae) is a hazardous, blood-sucking ectoparasite of birds that constitutes a threat to poultry farming worldwide. Acaricides, commonly used in poultry farms to prevent PRMs, are not effective because of the rapid emergence of acaricide-resistant PRMs. However, vaccination may be a promising strategy to control PRM. We identified a novel cystatin-like molecule in PRMs: Dg-Cys. Dg-Cys mRNA expression was detected in the midgut and ovaries, in all stages of life. The PRM nym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 41 publications
2
11
0
Order By: Relevance
“…On the other hand, the probe specific to the Dg-Cys gene successfully detected its expression in the intestinal tract and ovaries ( Fig. 2B ), consistent with a previous report [ 8 ]. These data suggest that the RNAscope ISH assay can be applied for expression analysis in different tissues.…”
supporting
confidence: 90%
See 3 more Smart Citations
“…On the other hand, the probe specific to the Dg-Cys gene successfully detected its expression in the intestinal tract and ovaries ( Fig. 2B ), consistent with a previous report [ 8 ]. These data suggest that the RNAscope ISH assay can be applied for expression analysis in different tissues.…”
supporting
confidence: 90%
“…Cystatin is an inhibitor of cysteine proteases and is involved in the regulation of tick-host interactions and blood digestion in ticks [ 10 , 21 ]. Our previous study confirmed the expression of Dg-Cys in the digestive tract and ovaries by LCM and RT-PCR [ 8 ].…”
supporting
confidence: 80%
See 2 more Smart Citations
“…Other proteins were selected because they are homologue to proteins used in tick vaccines (154,155). Antigen cocktails and whole-mite extracts have also been used (156,157).…”
Section: Vaccines Against Other Parasitesmentioning
confidence: 99%